Number of Ovarioles in Workers of Apis Mellifera Adansonii and Apis Mellifera Ligustica: A Comparative Study - Chaud-Netto, José [UNESP]; Bueno, Odair Correa [UNESP] (Taylor & Francis, 1979)
Worker pupae of Apis mellifera ligustica and A. m. adansonii (330 of each) were dissected, and their ovaries excised. For each race, the mean number of ovarioles in the right and left ovaries were significantly different; in both, the left ovary had more ovarioles than the right. Significant differences were found between races, and between samples of the same race, for number of ovarioles in the right (and in the left) ovary, and in both together. In all groupings, the mean numbers of ovarioles were significantly greater in A. m. ligustica than in A. m. adansonii. © 1979 International Bee Research Association.